First Detection of the Crayfish Plague Pathogen Aphanomyces astaci in Costa Rica: European Mistakes Should Not Be Repeated - Martín-Torrijos, Laura; Correa-Villalona, Angel Jose; Azofeifa-Solano, Juan Carlos; Villalobos-Rojas, Fresia; Wehrtmann, Ingo S.; Diéguez-Uribeondo, Javier (Frontiers in Ecology and Evolution, 2021)
The crayfish plague pathogen Aphanomyces astaci is one of the main factors responsible for the decline in European and Asian native crayfish species. This pathogen was transported to these regions through its natural carriers, North American crayfish species, which were introduced during the last century. Since then, the carrier species and the pathogen have spread worldwide due to globalization and the highly invasive nature of these species. In Europe, five carrier species have been categorized as high-risk as they are responsible the loss of provisioning services, which endangers freshwater ecosystems. The red swamp crayfish Procambarus clarkii, in particular, is currently one of the most concerning species as its spread threatens crayfish biodiversity and freshwater ecosystems worldwide. In this study, we describe the first detection of A. astaci in an introduced population of P. clarkii in Central America, specifically in Costa Rica. Using molecular approaches, we analyzed 48 crayfish samples collected from Reservoir Cachí and detected the presence of A. astaci in four of these samples. The introduction of P. clarkii and the incorrect management of the species (related to its fishery and the commercialization of live specimens) over the past decades in Europe are mistakes that should not be repeated elsewhere. The detection of the pathogen is a warning sign about the dangerous impact that the introduction of this invasive crayfish may have, not only as a carrier of an emerging disease but also as a direct risk to the invaded ecosystems. Our results may serve to (1) assess current and future consequences, and (2) direct future research activities, such as determining the potential impacts of A. astaci on native decapod species, or on other introduced crayfish species that are used for aquaculture purposes, such as Cherax quadricarinatus.